Noise spectra and dark current investigations in n⁺-p-type Hg₁₋xCdxTe (x ≈ 0.22) photodiodes - Ivasiv, Z.F.; Sizov, F.F.; Tetyorkin, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The dark current and noise spectra were investigated in Hg₁₋xCdxTe (x≅0.22) photodiodes at zero and low reverse bias voltages. The photodiodes were prepared by boron implantation into LPE films. The 1/f noise is proved to be correlated with tunneling current via the deep defect states in the gap at low reverse biases U≤0.1 V. In the photodiodes, where the tunneling current is found to be dominating, the 1/f noise is observed up to frequencies 10⁴ Hz. The decrease of tunneling current results in the decrease of 1/f noise.